2008
DOI: 10.1002/jnr.21878
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐Dihydroxyvitamin D3 administration to 6‐hydroxydopamine‐lesioned rats increases glial cell line‐derived neurotrophic factor and partially restores tyrosine hydroxylase expression in substantia nigra and striatum

Abstract: It has previously been demonstrated that 1,25-dihydroxyvitamin D(3) [1,25(OH)(2)D(3)] administration, whether in cell cultures or in vivo to rats, increases glial cell line-derived neurotrophic factor (GDNF) expression levels, suggesting that this hormone may have beneficial effects in neurodegenerative disorders. This study was carried out to explore the effects of 1,25(OH)(2)D(3) administration in a 6-OHDA-lesioned rat model of Parkinson's disease on GDNF and tyrosine hydroxylase (TH) expression in substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 33 publications
1
76
0
4
Order By: Relevance
“…In rodents, the neurotoxin 6-hydroxydopamine (6-OHDA) removes dopaminergic neurons in a specific manner and produces PD-like symptoms (Burns et al 1983). There are several studies in rats examining the effects of neuroprotectives to a systemic administration of 6-OHDA (Baluchnejadmojarad et al 2009;Sanchez et al 2009). Similarly, in C. elegans, exposure to 6-OHDA induces programmed cell death in dopaminergic neurons (Cao et al 2005;Nass et al 2002) and complete neuronal destruction if rotenone, a plant neurotoxin in mammals (Alam and Schmidt 2002), was also administered (Schmidt et al 2007).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…In rodents, the neurotoxin 6-hydroxydopamine (6-OHDA) removes dopaminergic neurons in a specific manner and produces PD-like symptoms (Burns et al 1983). There are several studies in rats examining the effects of neuroprotectives to a systemic administration of 6-OHDA (Baluchnejadmojarad et al 2009;Sanchez et al 2009). Similarly, in C. elegans, exposure to 6-OHDA induces programmed cell death in dopaminergic neurons (Cao et al 2005;Nass et al 2002) and complete neuronal destruction if rotenone, a plant neurotoxin in mammals (Alam and Schmidt 2002), was also administered (Schmidt et al 2007).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…For detection we used EnVision FLEX/HRP (Dako). Quantitation of immunopositive cells for active caspase-3 expression was performed as previously described (56).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, many studies of PD models have demonstrated roles for vitamin D in neuronal cell differentiation and neuroprotection via various mechanisms [17,18,19,20,21]. Therefore, vitamin D may be neuroprotective against PD-related degenerative processes in the dorsal motor vagal system and enteric nervous system, indicating that vitamin D plays an important role in gastric dysmotility in PD.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have demonstrated an additional role for vitamin D in neuroprotection through various mechanisms, including antioxidation, neuronal calcium regulation, immunomodulation, enhanced nerve conduction, detoxification and autophagy [16,17,18,19,20,21]. Furthermore, vitamin D has recently been suggested to be involved in the pathogenesis and progression of PD [22], and recently, we reported that vitamin D levels were associated with orthostatic hypotension in PD patients [23].…”
Section: Introductionmentioning
confidence: 99%